Particularities of trichloroethylene photocatalytic degradation over crystalline RbLaTa2O7 nanowire bundles grown by solid-state synthesis route. Issue 1 (February 2019) - Raciulete, Monica; Papa, Florica; Kawamoto, Daisuke; Munteanu, Cornel; Culita, Daniela C.; Negrila, Catalin; Atkinson, Irina; Bratan, Veronica; Pandele-Cusu, Jeanina; Balint, Ioan
Graphical abstract: Highlights: RbLaTa2 O7 nanowire and platelets are obtained by solid-state reaction method. Morphology of layered RbLaTa2 O7 is tuned by optimization of synthesis conditions. Strong surface basicity and high density −OH favors photomineralization of TCE. Weak basicity lead to preferential formation of intermediate chlorinated compounds. Abstract: This is the first report on synthesis and photocatalytic activity for trichloroethylene (TCE) degradation under simulated solar light over RbLaTa2 O7 layered perovskites with predominant nanowire or platelet morphologies. SEM images witnessed that the one step thermal treatment at 1200 °C lead to formation of RbLaTa2 O7 nanowires with diameter of 80–320 nm and several microns in length associated in bundles and sharp-edged, merged platelets (minor phase). The two-step annealing at 950 °C and 1200 °C resulted in decrease of wires bundle population and increase in that of platelets merged in facetted particles. The RbLaTa2 O7 nanowires are made of by well-aligned atomic rows with preferred orientation toward the c-axis, relatively free of defect. High density of hydroxyl groups on the sample calcined in mild conditions (RbLaTa_01) favors the photo mineralization of TCE. In contrast, the activity of RbLaTa_02 annealed in harsh conditions (950 and 1200 °C), poor in surface hydroxyl groups, remained modest. The weak surface basicity directed the reaction mainly to generation of intermediate chlorinated compounds. Pd and Au were supported on RbLaTa2 O7 perovskites as an alternative strategy to boost the removal of chlorinated pollutants by combining photocatalytic (mineralization) and catalytic (hydrodechlorination, HDC) processes. The mineralization of TCE to Cl − was drastically hindered in presence of methanol due to quenching of ⋅OH radicals by alcohol. The results suggested that the density of RbLaTa2 O7 surface hydroxyl groups is essential for photo mineralization of TCE whereas the surface carbonate is beneficial for the formation of intermediate chlorinated product.